Recent defect passivation drifts and role of additive engineering in perovskite photovoltaics. (October 2022) - Hassan, Ali; Wang, Zhijie; Ahn, Yeong Hwan; Azam, Muhammad; Khan, Abbas Ahmad; Farooq, Umar; Zubair, Muhammad; Cao, Yu
Abstract: Rapid progress in the efficiency of hybrid lead halide perovskite photovoltaics surpassed the semiconductor thin-film solar cells such as CdTe (cadmium telluride), CZTS (copper zinc tin sulfide), and CIGS (copper indium gallium selenide) within a decade. Furthermore, low-cost solution processibility demonstrated the immense potential of perovskite solar cells (PSCs) as an alternative to commercially available light-harvesting materials. Despite the fast-track development in perovskite photovoltaic technology, several drawbacks are mainly linked with defects, including undercoordinated ions, band offsets, grain boundaries, photocurrent hysteresis, and environmental instability: restraint the industrialization of perovskite photovoltaics. Herein, we present the comprehensive knowledge of the source, nature, correlation with photophysical properties, and overlapping effects of these defects. The defects are categorized based on their energy levels within the conduction and valence bands, such as deep or shallow level defects, and their dimensionality (e.g., point defects such as vacancies, dislocation, grain boundaries, and cracks are regarded as zero-, one-, two-, and three-dimensional defects). Furthermore, we developed the fundamental understanding of defect-mediated, nonradiative recombination, ion migration, carrier trapping, and their cross-link with device performance and photocurrent hysteresis. Besides, an overview of topical defect passivation strategies on perovskite absorber, materials interface, charge transport layers, surface passivation, contact passivation, and additive engineering has been spotlighted. Finally, based on past and present defect healing drifts, we have summarized and recommended suggestions for next-generation PSCs, which will pave the way for swift industrialization. Graphical Abstract: ga1 Highlights: A comprehensive review covering all physical and chemical defects and their origin in perovskite solar cells. Significance of additive engineering to passivate the surface and interface defects. A detailed analysis and suggestion for future research prospective to boost the efficiency of perovskite energy harvesters.